(untitled) (Orinoquia, 2018)
The understanding of the migratory events in freshwater fish is fundamental to know their biology and ecology, since these natural events lead to generate alternatives for the management and preservation of fisheries, especially in species that present challenges due to their great capacity of displacement in the entire Amazon basin. The large catfish of the Pimelodidae family are characterized by presenting these migratory characteristics, which are influenced by the flood pulse, where the amaincrease of waters due to heavy rainfall in the headwaters raises the level of the waters, stimulating them to initiate migrations and to carry performed the process of gonadal maturation, inducing individuals to go to spawning areas upstream to complete their reproductive process. The objective of the present review, aims to address in a general way to deal with aspects involved in the migration of Siluriform fishes and their relationship with hydrological cycles.